2006
DOI: 10.1167/iovs.05-0650
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Proteasome in TGF-β Signaling in Lens Epithelial Cells

Abstract: The HLE B-3 cell line and primary cultured human lens cells respond similarly to TGF-beta treatments by activating cataract-related gene expression. This response in both of these model systems is blocked by inhibiting the proteasome. This suggests that the proteasome can mediate cataract and PCO-associated changes and therefore is a novel target of medical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…The 26S proteasome is a ~2500 kDa complex consisting of one 20S core particle (CP) and two 19S regulatory particles (RPs) (Murata et al, 2009). Previous studies using in vitro cultures showed that the UPS is required for the proliferation of lens epithelial cells (Guo et al, 2006), mitochondrial degradation during lens fiber differentiation (Zandy and Bassnett, 2007), TGF-mediated lens fiber cell differentiation (Wu et al, 2007) and posterior capsular opacification (Hosler et al, 2006). It was reported that the UPS cooperates with a chaperone system to control protein quality (Bian et al, 2008;Bornheim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The 26S proteasome is a ~2500 kDa complex consisting of one 20S core particle (CP) and two 19S regulatory particles (RPs) (Murata et al, 2009). Previous studies using in vitro cultures showed that the UPS is required for the proliferation of lens epithelial cells (Guo et al, 2006), mitochondrial degradation during lens fiber differentiation (Zandy and Bassnett, 2007), TGF-mediated lens fiber cell differentiation (Wu et al, 2007) and posterior capsular opacification (Hosler et al, 2006). It was reported that the UPS cooperates with a chaperone system to control protein quality (Bian et al, 2008;Bornheim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The SV-40 virus immortalized human lens epithelial cell line HLE B-3 was selected for use in the coculture model. Although differences between the proteomes of native lens epithelial cells and HLE B-3 have been investigated, namely the absence of crystalline expression in HLE B-3, 56 the cell line continues to be used extensively to study signaling pathways and mechanisms in PCO, 12,15,16,42,43,57 and capsular biocompatibility with IOL materials. 58,59 Our objective was to examine the uveal biocompatibility of PMMA and pHEMA IOL materials by quantifying cellular activation.…”
Section: Discussionmentioning
confidence: 99%
“…5 Chung et al 42 showed that treatment with TGF-b 1 induced fibronectin expression in HLE B-3 cells, while Hosler et al 16 showed that treatment with TGF-b 2 induced fibronectin gene activation in HLE B-3 and primary cells. Choi et al 12 observed that TGF-b 1 treatment repressed E-cadherin expression in HLE B-3 cells, while a similar study by Yao et al 82 observed the same finding but in alveolar epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that the proteasome can mediate ASC cataract [84,85]. The HLE B-3 cell line and primary cultured human lens cells respond similarly to TGF-β treatments by activating cataract-related gene expression and this response was blocked by inhibiting the proteasome, suggesting that proteasome inhibitors could be candidates for blocking development of PCO.…”
Section: Proteases In Pcomentioning
confidence: 99%